Reactivity of O-Drug Bond in some Suggested Voltarine Carriers: Semiempirical and ab Initio Methods (Baghdad Science Journal, 2021)
In this work, the possibility to use new suggested carriers (D= Aspirin, Ibuprofen, Paracetamol, Tramal) is discussed for diclofenac drug (voltarine) by using quantum mechanics calculations. The calculation methods (PM3) and (DFT) have been used for determination the reaction path of (O-D) bond rupture energies. Different groups of drugs as a carrier for diclofenac prodrugs (in a vacuum) have been used; at their optimized geometries. The calculations included the geometrical structure and some of the physical properties, in addition to the toxicity, biological activity, and NLO properties of the prodrugs, investigated using HF method. The calculations were done by Gaussian 09 program. The comparison was made for total energies of reactants, activation energies, and transition states to final products. The suggested prodrugs aim to improve the diclofenac carrier's properties and obtain new alternatives for the approved carriers theoretically.